Satisfaction Among Recipients of Cosmetic Facial Filling Procedures at Dermatology Clinics in Saudi Arabia: A National Study - Al-Atif HM; Alqarni AM; Almuntashiri AA; Almuntashiri AS; Almarhabi MA (Dove Medical Press, 2024)
Hend M Al-Atif,1 Abdulrhman Mohammed Alqarni,2 Abdularhman Abdullah Almuntashiri,2 Ali Saad Almuntashiri,2 Maram Ahmed Almarhabi2 1Department of Internal Medicine, College of Medicine, King Khalid University, Abha City, Kingdom of Saudi Arabia; 2Faculty of Medicine, Umm Al Qura University, Al Qunfudhah Medical College, Makkah, Saudi ArabiaCorrespondence: Hend M Al-Atif, Associate Professor, Department of Internal Medicine, College of Medicine, King Khalid University, Abha City, Kingdom of Saudi Arabia, Email hotaif@kku.edu.saPurpose: Facial cosmetic procedures, known for their rising popularity, frequently yield high patient satisfaction. However, certain patient characteristics may influence this satisfaction. Additionally, patients' satisfaction can affect their attitudes and preferences toward these procedures and recommendations to others. Our study aimed to assess post-procedure satisfaction among individuals who have undergone cosmetic facial filling procedures at dermatology clinics.Patients and Methods: This cross-sectional study targeted the Saudi population who had undergone cosmetic facial filling procedures, excluding individuals under 18, those with a history of mental health disorders, or invasive surgical procedures, as well as those unable or unwilling to provide informed consent. Data were collected using a comprehensive questionnaire covering demographics, procedure details, satisfaction, and future plans. A 5-point Likert scale was used to assess self-perception and satisfaction. The questionnaire was developed after expert consultation and a literature review, with overall satisfaction calculated as the mean of all items.Results: In this study of 408 participants in Saudi Arabia, predominantly young, unmarried females, high satisfaction levels were observed following cosmetic facial filling procedures, with a mean score of 3.9 for procedure results and 3.8 for meeting expectations. Most participants were Saudi nationals (97.8%), aged below 25 (41.7%), and held Bachelor's degrees (80.6%), with a majority being females (87.7%). Notably, factors significantly affecting overall satisfaction included gender (p = 0.001), marital status (p = 0.023), income (p = 0.031), procedure duration (p = 0.003), and procedure type (p = 0.046). These findings offer crucial insights for enhancing patient experiences and outcomes in cosmetic facial filling procedures.Conclusion: This study unveiled substantial self-satisfaction levels, particularly regarding appearance and social well-being, emphasizing the significance of informative pre-procedure guidance, while gender, marital status, income, procedure duration, and type significantly impacted satisfaction. Healthcare providers must heed these factors to enhance patient contentment and overall procedure success.Keywords: cosmetic procedures, patient satisfaction, noninvasive procedures, Saudi Arabia, self-esteem